2018
DOI: 10.1063/1.5041986
|View full text |Cite
|
Sign up to set email alerts
|

Generation of second-harmonic Ince-Gaussian beams

Abstract: As a continuous transition between the Hermite-Gaussian and Laguerre-Gaussian beams, the Ince-Gaussian beams form a family of exact orthogonal solutions of the free-space paraxial wave equation in elliptic coordinates. Ince-Gaussian beams have multiple transverse mode patterns, which make them unique in terms of application in the fields of bioengineering, particle manipulation, and quantum entanglement. Here, based on binary nonlinear computer-generated holograms with a domain structure (realized via electric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…However, there have been few reports on this topic, such as ref. 29 reported generation second-harmonic IG modes by adding diffraction gratings on the crystal, and in particular, a quantitative selection rule of IG modes during nonlinear transformation is still a research gap to date.…”
mentioning
confidence: 99%
“…However, there have been few reports on this topic, such as ref. 29 reported generation second-harmonic IG modes by adding diffraction gratings on the crystal, and in particular, a quantitative selection rule of IG modes during nonlinear transformation is still a research gap to date.…”
mentioning
confidence: 99%
“…In order to encode the designed DVG phase mask to the quadratic susceptibility of LN nonlinear crystal, the electric poling method is adopted in the sample preparation process. [38,39] The +z face of a z-cut LN slice is covered with a 120-nm-thick Cr electrode having the designed DVG pattern, through the process of maskless photolithography, vacuum deposition, and photoresist removal. High voltage pulses slightly larger than the coercive field of the used 50-µm-thick LN slice are applied to convert the spontaneous polarization directions.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al [ 15 ] demonstrated Ince–Gaussian-beam array generation by using a computer-generated hologram (CGH) and spatial light modulator (SLM). A second harmonic Ince–Gaussian beam generation was reported by Wang et al [ 16 ] by employing a binary non-linear CGH. Ohtomo et al [ 17 ] demonstrated a method to generate vortex, HG and IG beams, and also the conversion of one structural beam to another using an astigmatism mode converter (AMC).…”
Section: Introductionmentioning
confidence: 99%